Dancing with the landscape. Anna Halprin ‘explorative’ dance as the encounter with nature’s and architecture’s atmospheric affordances (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Following Jean-Marc Besse’s identification of landscape as a dynamic, changing, relational and ‘emergent’ entity, I argue in this article that the artistic creative process is a way of ‘doing with’ landscape that fully embraces this peculiarity of landscape. The art of dance, in particular, makes it clear that it is the artist who creates a kind of mutual attraction between the (trans)formative forces of the landscape, suggesting its renewal and thus giving impetus to its metamorphic and transformative nature. Drawing on Tonino Griffero’s neo-phenomenological approach to the characterisation of landscape as an atmosphere, i.e. as an emotional tonality effused in a ‘felt-bodily’ space, I emphasise the role of the affective dimension in the perception of landscape as something ‘to do with’ rather than ‘to act upon’ in artistic practice. To this end, I take as a case study Anna Halprin’s ‘exploratory’ dance, which focuses on fostering an individual and collective search for a harmonisation of the relationship between movement and emotion. Drawing on notions of the ‘felt body’, ‘atmospheric affordances’ and ‘ecstasies of things’, I analyse the role that her outdoor dance studio – designed by landscape architect Lawrence Halprin – plays in placing the creative process at the centre of dance’s very specific way of ‘doing with’ the landscape.